Symptoms of the risk of mobile phone addiction and symptoms of mobile phone addiction in Polish young people aged 13 to 24 years measured using Potembska and Pawłowska’s Mobile Phone Addiction Assessment Questionnair - Pawłowska, Beata; Potembska, Emilia (Current Problems of Psychiatry, 2012)
The aim of this study was to determine the prevalence of mobile phone addiction and of the risk of mobile phone addiction in young peo-ple aged 13–24 years on the basis of their scores on Potembska and Pawłowska’s Mobile Phone Addiction Assessment Questionnaire.Participants: The study was conducted in the years 2010–2011 and included a group of 694 young people aged 13 to 24 years. 206 of the participants (67 boys and 139 girls) attended a secondary school, 113 (48 boys and 65 girls) attended a gymnasium, and 375 were university students (123 men and 252 women).Methods: The study was conducted using a socio-demographic questionnaire and the Mobile Phone Addiction Assessment Questionnaire (KBUTK) by Potembska and Pawłowska. KBUTK consists of 33 items. The coefficients of reliability for the individual scales were high: Cronbach’s alpha=0.91 for the Acceptance and Closeness scale; Cronbach’s alpha=0.81 for Addiction to Mobile Phone Features; Cronbach’s alpha=0.85 for Addiction to Text Messaging and Voice Calls; and Cronbach’s alpha=0.83 for Indirect Communication. The reliability coefficient for the global KBUTK score was 0.91. A test-retest was performed within one month on a group of 65 persons and the following correlation coefficients were obtained for the individual scales: Acceptance and Closeness scale, rtt=0.79, (p